Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
Bài 1 Từ \(\left|x-1\right|=2\) \(\Rightarrow\left\{{}\begin{matrix}x-1=2\\x-1=-2\end{matrix}\right.\)\(\Rightarrow\left\{{}\begin{matrix}x=2+1\\x=-2+1\end{matrix}\right.\)\(\Rightarrow\left\{{}\begin{matrix}x=3\\x=-1\end{matrix}\right.\)
Với x = 3 \(\Rightarrow A=3\cdot3^2-4\cdot3+1\)
\(A=3\cdot9-12+1\)
\(A=27-12+1=16\)
Với x = -1 \(\Rightarrow A=3\cdot\left(-1\right)^2-4\cdot\left(-1\right)+1\)
\(A=3\cdot1-\left(-4\right)+1\)
\(A=3+4+1=8\)
Bài 2
a) \(\left|x-10\right|=-x+10=10-x\)
\(\left|x-10\right|=10-x\) \(\Leftrightarrow x-10\le0\) \(\Leftrightarrow x\le10\)
b)\(\left|\dfrac{x-1}{1-x}\right|=1\)
\(\Rightarrow\left\{{}\begin{matrix}\dfrac{x-1}{1-x}=1\\\dfrac{x-1}{1-x}=-1\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x-1=1-x\\x-1=-1+x\end{matrix}\right.\)\(\Rightarrow\left\{{}\begin{matrix}x+x=1+1\\x-x=-1+1\end{matrix}\right.\)\(\Rightarrow\left\{{}\begin{matrix}2x=2\\0=0\end{matrix}\right.\Rightarrow\left\{{}\begin{matrix}x=2:2=1\\x\in Z\end{matrix}\right.\)
d)\(\left|x-4\right|+\left(3+3\right)=7\)
\(\left|x-4\right|+6=7\)
\(\left|x-4\right|=7-6\)
\(\left|x-4\right|=1\)
\(\Rightarrow\left\{{}\begin{matrix}x-4=1\\x-4=-1\end{matrix}\right.\) \(\Rightarrow\left\{{}\begin{matrix}x=1+4\\x=-1+4\end{matrix}\right.\)\(\Rightarrow\left\{{}\begin{matrix}x=5\\x=3\end{matrix}\right.\)
\(x^3-3x^2+3x-1=\left(x-1\right)^3\)
\(a,x=-2\Leftrightarrow A=\left(x-1\right)^3=\left(-2-1\right)^3=-3^3=-27\)
\(b,x=\frac{1}{2}\Rightarrow A=\left(x-1\right)^3=\left(\frac{1}{2}-1\right)^3=\left(-\frac{1}{2}\right)^3=-\frac{1^3}{2^3}=-\frac{1}{8}\)
Vì: | 5x - 3 | \(\ge0\)
\(\left(\frac{1}{2}y-27\right)^{108}\ge0\)
( 37x + 2 )10 \(\ge0\)
Để \(\left|5x-3\right|+\left(\frac{1}{2}y-27\right)^{108}+\left(37x+2\right)^{10}=0\)
<=> | 5x - 3 | = 0
5x = 3
x = 3/5
<=> \(\left(\frac{1}{2}y-27\right)^{108}=0\) khi \(\frac{1}{2}y-27=0\)
1/2y = 27
y = 54
<=> ( 37x + 2 )10 = 0
37x + 2 = 0
37x = -2
x = -2/37
KL: x,y,x = ........................................
a) (2x + 3)(x - 4) + (x - 5)(x - 2) = (3x - 5)(x - 4)
<=> 2x2 - 5x - 12 + x2 - 7x + 10 = 3x2 - 17x + 20
<=> 5x = 22
<=> x = 22/5
b) (8x - 3)(3x+ 2) - (4x + 7)(x + 4) = (2x + 1)(5x- 1)
<=> 24x2 + 7x - 6 - 4x2 - 23x - 28 = 10x2 + 3x - 1
<=> 10x2 - 19x -33 = 0
<=> 10x2 - 30x + 11x - 33 = 0
<=> (10x + 11)(x - 3) = 0
<=> \(\orbr{\begin{cases}10x+11=0\\x-3=0\end{cases}}\) <=> \(\orbr{\begin{cases}x=-\frac{11}{10}\\x=3\end{cases}}\)
c) 2x2 + 3(x - 1)(x + 1) = 5x(x + 1)
<=> 2x2 + 3x2 - 3 = 5x2 + 5x
<=> 5x = -3
<=> x = -3/5
Ta có:
\(\frac{3^2}{0,375^2}\)
=\(\frac{9}{0.140625}\)
=64
\(3^x+3^{x+1}=108\)
\(\Rightarrow3^x.1+3^x.3^1=108\)
\(\Rightarrow3^x.\left(1+3^1\right)=108\)
\(\Rightarrow3^x.4=108\)
\(\Rightarrow3^x=108:4\)
\(\Rightarrow3^x=27\)
\(\Rightarrow3^x=3^3\)
\(\Rightarrow x=3\)
Vậy \(x=3.\)
Chúc bạn học tốt!
3x+3x+1=108
<=>3x+3x.3=108
<=>3x(1+3)=108
<=>3x.4=108
<=>3x=108:4
<=>3x=27
<=>3x=33
=>x=3
Vậy x=3
Chúc bạn học tốt